Structural Barriers to the Implementation of Christian Religious Education in Indonesian Public Schools: A Policy and Institutional Practice Analysis - Ohira Ohira (Jurnal Didaskalia, 2026)
Christian Religious Education (CRE) in Indonesian public schools faces layered and systemic structural barriers. This study aims to analyze these barriers from the perspectives of educational policy and institutional practice. A qualitative approach with literature review and policy document analysis was employed. Data were gathered from academic journals, regulatory documents, government reports, and verified media coverage. The study identifies five primary barriers: (1) educational management dualism between the Ministry of Religious Affairs and Regional Education Offices, generating institutional responsibility ambiguity; (2) a significant CRE teacher deficit with a ratio of 1:8.5 teachers per public school; (3) inadequate learning facilities and infrastructure; (4) structural discrimination against CRE teachers in appointment, certification, and welfare; and (5) discrimination against Christian students in school operational practices. These findings indicate that root causes lie not merely in technical implementation but in flawed policy design and cross-sectoral coordination failure. Comprehensive policy reform is urgently required, including revision of inter-agency coordination mechanisms, strengthening of CRE teacher recruitment and welfare systems, and enforcement of monitoring mechanisms for religious minority students' rights in public schools.